Permeation and Rectification in Canonical Transient Receptor Potential-6 (TRPC6) Channels - Dryer, Stuart E.; Kim, Eun Young (Frontiers in Physiology, 2018)
TRPC6 channels are widely expressed cation channels that play a role in regulating Ca2+ dynamics, especially during G protein-coupled receptor signaling. The permeation of cations through TRPC6 is complex and the relative permeability to Ca2+ relative to monovalent cations appears to be highly voltage-dependent and is reduced upon membrane depolarization. Many investigators have observed complex current-voltage (I-V) relationships in recordings of TRPC6 channels, which often manifest as flattening of I-V curves between 0 and + 40 mV and negative to -60 mV. These features are especially common in recordings from TRPC6 channels expressed in heterologous expression systems. Indeed, it is sometimes argued that marked rectification at both negative and positive membrane potentials is a defining feature of TRPC6, and that recordings in which these features are reduced or absent cannot reflect activity of TRPC6. Here we present a review of the literature to show that complex rectification is not seen in every cell type expressing TRPC6, even when comparing recordings made from the same groups of investigators, or in recordings from what is nominally the same heterologous expression system. Therefore other criteria, such as gene knockout or knockdown, or the use of newly emerging selective blockers, must be used to ascertain that a given current reflects activity of endogenously expressed TRPC6 channels. We also discuss the possibility that complex rectification may not be an intrinsic property of TRPC6 in cells where it is observed, and may instead reflect presence of endogenous substances that cause voltage-dependent inhibition of the channels.